Influence of street-art on the formation of city image and the principles of street-art geographical zones - Maslyak, P. O.; Gryniuk, O. Y.; Kazantseva, K. A. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
The time when any drawing, inscription in the streets of Kyiv was considered as graffiti has passed, and now the city is covered with the works of good quality as the famous pieces of art. These art projects change the usual images of houses, streets and districts of the city for ordinary citizens. Its space is modified and it seems to get the other way of perception.The research objective is to study the features of street-art facilities geospatial location in Kyiv, the possibility to use these objects in tourism and recreation, explore how image and silhouette of the city will change with graffiti and other street-art facilities, to offer basic principles of street-art zoning.The objectives of the article: to analyse street-art artifacts in Kyiv for their artistic value and appropriateness of using them as the components in the formation of urban environment as well as the use of graffiti in tourist activity including the development of sightseeing route network in Kyiv.The methodological basis is the analysis of in-depth interview, analysis of previous texts and examination of conducted sociological surveys. The interview contains the elements of street-art and their perception by locals and tourists.This paper investigates the influence of contemporary street-art on formation of the tourist image of the city. The study shows that street-art has a beneficial effect on the tourist image of the city and changes townspeople's impression of the usual space.Purposive systemic territorial organization of street-art has a great role in forming the city image. Today in the capital of Ukraine this systematization is limited with finding appropriate topics for murals and proper places for their creation. Nobody knows how it will or would look like in the context and process of purposive formation of spatial and territorial image of the city in the nearest future.Murals could probably be divided into two groups. The first one creates modern urban environment for residents. The other works mainly for tourists. They almost do not coincide geographically. The first group is mainly focused on the residential areas with new buildings, the second – on the central parts of the city. They are losing the resident population and are gradually transforming into a tourist environment.